Effect of Addition of Patchouli Leaf Essential Oil (Pogostemon cablin benth) on Eyecream Products - Arahman, Nasrul; Deski, Dhafin; Akbar, Awalul; Surya, Alit; Pitra, Muhammad Novan; Pratama, Raihan Nanda (Universitas Syiah Kuala, 2023)
Free radicals are one of the factors that cause skin problems. Excessive exposure to free radicals can trigger aging, such as sagging of the skin of the lower eyelids which causes a decrease in the periorbital area, known as “eyelid bags”. Changes in the extracellular matrix and loss of the structurally important proteins collagen and elastin lead to loss of structural support and elasticity. Free radical reactions can be prevented by using eye cream. Eye cream is made to get rid of puffiness or dark circles under the eyes. Eye cream is made from a light, easy-to-absorb formula and contains vitamin C, vitamin E and vitamin K which are good for skin care and rejuvenation. This study aims to determine the effectiveness of the Gayo avocado oil eyecream formulation with the addition of patchouli leaf essential oil. The method used is experimental from the results of research that has been done before. Then three stages of testing were carried out, namely irritation test, organoleptic test and characteristic observation test. Then, for the test results, a comparison of the first and second formulations was carried out to determine which eye cream is suitable for use as a beauty product